2014
DOI: 10.1111/ijfs.12657
|View full text |Cite
|
Sign up to set email alerts
|

Refining of edible oils: a critical appraisal of current and potential technologies

Abstract: Summary The major sources of dietary lipids are edible oils, which include both vegetable and fish oils. Crude oil extracted from vegetable and fish sources contain mono‐, di‐, triacylglycerols along with impurities, which necessitates refining. The main objective of refining is to remove the contaminants that adversely affect the quality of oil, thereby reducing the shelf life and consumer acceptance. However, this refining process needs to be tailored as the composition of crude oil is highly variable, depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 96 publications
1
82
0
6
Order By: Relevance
“…Degumming is the initial step in edible oil refining which removes phospholipids and some portion of trace metals and mucilaginous substances 9 . Sardine oil was degummed through an acid degumming process by considering various acids like OPA, LA and AC.…”
Section: Degummingmentioning
confidence: 99%
See 2 more Smart Citations
“…Degumming is the initial step in edible oil refining which removes phospholipids and some portion of trace metals and mucilaginous substances 9 . Sardine oil was degummed through an acid degumming process by considering various acids like OPA, LA and AC.…”
Section: Degummingmentioning
confidence: 99%
“…Chemical refining has many disadvantages such as high-energy demand, nutrient loss, need for large quantities of water and chemicals, and disposal of polluted effluents. Enzymatic treatment employed to refine the crude oil is effective and ecofriendly, but seldom applied for industrial purposes due to cost constraints 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this theory has recently faced challenges, as some studies report inconsistent results. This was attributed to the wide variation in the fatty acid and triglyceride content in bulk oil systems (Vaisali, Charanyaa, Belur, & Regupathi, 2015). Further study of bulk oil revealed colloidal structures with many hydrophilic and hydrophobic regions.…”
Section: Introductionmentioning
confidence: 99%
“…Crude camellia seed oil also contains plenty of free fatty acids, which must be removed to obtain an oil of acceptable quality. In conventional edible oil‐refining steps, free fatty acids are precipitated as soaps and removed by alkali refining during deacidification . However, the soapstock can hold neutral oil, which leads to losses.…”
Section: Introductionmentioning
confidence: 99%